A Convenient Synthesis of 9-(2-Hydroxyethoxymethyl)guanine (Acyclovir) and Related Compounds - YAMADA, KEIKO; MORI, TAKEO; MATSUMOTO, HIROATSU; TAKEUCHI, TADAO; MIZUNO, YOSHIHISA; KANEKO, CHISATO (Chemical & pharmaceutical bulletin, 1988)
A convenient and economical synthesis of 9-(2-hydroxyethoxymethyl)guanine (1, acyclovir, Zovirax, or acyclic guanosine : an antiherpetic agent)from guanine was developed via N2, O-diacetylacyclovir. Two closely related compounds, N2-acetylacyclovir (7) and O-acetylacyclovir (8), were also prepared by selective deacetylation.